The Effect of Caulerpa Cylindracea Extract on Histopathology Depiction of Male Rattus Norvegicus Gaster Mucosa Induced by Indomethacin - FITRI HANDAJANI; Adya Hidayatullah; Nita Pranitasari (Medical and Health Science Journal, 2021)
ABSTRACT